Cerebral hemorrhage with ventricular flood: emergency surgical treatment - Palma, Eduardo C; Rius, Mario; Pollero, Héctor; Arias, José; Corio, Ernesto; Pérez Lagrave, Alberto; Palma, Liliana (Cirugía del Uruguay, 1976)
The authors present a case of severe and progressive cerebral haemorrhage due to the rupture of an angioma with arterio-venous fistula, which provÓked a ventricular flooding. The patient was operated in the emergency, within 32 hours, with good results. Cerebral hemorrhage with ventricular flooding is not necessarily fatal when it receives a surgical treatment. 'Ihe treatment must be performed with great urgency in order to evacuate the ventricular and cerebral hemorrhage, o treat the originary lesion and to avoid new flowing of blood to the ventricles. The great entering permits the effective performance of the neurosurgical stages and at the same time makes the cerebral operative traumatism smaller. Local anesthesia minimizes the anesthetic agresion upon the nervous system. Re-opening of the incision (24 hours later) permits to make an early and exact postoperatory lesional evaluation, to treat immediately any complication and to withdraw the hemosthatic material left "in situ", all of which favours the good evolution of the patient.